From commitment to implementation: lessons learnt from the first National Strategy for the Reduction of Teenage Pregnancy in Sierra Leone. Issue 1 (1st January 2020) - Bash-Taqi, Regina; Watson, Katherine; Akwara, Elsie; Adebayo, Emmanuel; Chandra-Mouli, Venkatraman
Abstract: This study provides insight into the extent to which public commitment to reduce teenage pregnancy made by the President of Sierra Leone made the issue a political priority and the factors that facilitated and hindered this. Using historical observations from government and civil society actors who were involved in the formulation and implementation of the country's National Strategy for the Reduction of Teenage Pregnancy (NSRTP), the study presents lessons learnt, with a particular focus on advocacy. It does not examine the extent to which the NSRTP was operationalised and its objectives fulfilled. Findings indicate that the availability of locally relevant data as well as advocacy from international and national NGOs were factors that led to the President's commitment and the development of a national strategy. Whilst continued verbal support from political leaders and administrative mechanisms for implementation assured that teenage pregnancy reduction stayed on the political agenda, the scarcity of resources as well as the necessary diversion of efforts and resources to the Ebola epidemic impeded implementation. Overall, the findings demonstrate that public commitments made by political leaders – starting with President Ernest Bai Koroma's public declaration in 2012 – kick-started efforts to reduce teenage pregnancy in Sierra Leone; and that despite inadequate human and financial resources for the implementation of the NSRTP, actions taken by both the government and partners over time have contributed to tangible progress.